2020
DOI: 10.21203/rs.3.rs-91430/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and Safety of Arbidol in Treatment of Patients with COVID-19 Infection: A Randomized Clinical Trial

Abstract: Background: The outbreak of 2019-novel coronavirus has led to a high demand for finding effective antiviral agents. Preliminary experiments showed that Arbidol could inhibit coronavirus replication in vivo. There is limited data on the clinical efficacy of 2019-novel coronavirus-infected pneumonia (NCP). Therefore, we aimed to evaluate this medication based on clinical and laboratory results.Methods: The present study was designed as a clinical trial to investigate the advantages and disadvantages of this medi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…В отношении коронавируса SARS-CoV-2 механизм действия УМФ связан с блокированием этапа фузии на уровне взаимодействия поверхностного S-белка коронавирусов и рецептора АСЕ2 на поверхности клеток человека [16]. Результаты контролируемых рандомизированных исследований, проведенных в Иране, показали, что УМФ сокращает сроки десатурации и выздоровления пациентов, снижает частоту госпитализации в отделения интенсивной терапии [17,20]. Ретроспективные исследования также показывают, что прием УМФ снижал смертность госпитализированных пациентов [21] Применение препаратов ИФН в монотерапии или в комплексной ПВТ показало положительный эффект (уменьшение катаральных явлений и синдрома интоксикации), вероятно, связанный с недостаточным интерфероновым ответом на ранних этапах заболевания [23,24].…”
Section: Discussionunclassified
“…В отношении коронавируса SARS-CoV-2 механизм действия УМФ связан с блокированием этапа фузии на уровне взаимодействия поверхностного S-белка коронавирусов и рецептора АСЕ2 на поверхности клеток человека [16]. Результаты контролируемых рандомизированных исследований, проведенных в Иране, показали, что УМФ сокращает сроки десатурации и выздоровления пациентов, снижает частоту госпитализации в отделения интенсивной терапии [17,20]. Ретроспективные исследования также показывают, что прием УМФ снижал смертность госпитализированных пациентов [21] Применение препаратов ИФН в монотерапии или в комплексной ПВТ показало положительный эффект (уменьшение катаральных явлений и синдрома интоксикации), вероятно, связанный с недостаточным интерфероновым ответом на ранних этапах заболевания [23,24].…”
Section: Discussionunclassified
“…Furthermore, Li et al [106] concluded that ARB was superior to HCQ in terms of duration of hospital stay and SARS-CoV-2 negative conversion. Moreover, a randomized control trial proved the higher benefit in using ARB over HCQ, as it was responsible for the improvement of clinical symptoms and recovery rate [105].…”
Section: Arbidol (Arb)mentioning
confidence: 97%